Evocation to the Dr. Carlos J. Finlay Barres on the centennial of his death (Colombia Medica, 2016)
About the editorial of the Professor Guillermo Llanos: "Carlos J. Finlay: the forgotten Pasteur of America", a hundred years after his death and through a documental review, a summary of the life and work of this great man of science was conducted. Finlay was a notable figure of the American medicine, he conceived a new infection way able to explain the propagation of the yellow fever, and added the possibility of their scientific confirmation by an experimental method. For all the above-mentioned Finlay was recognized as the humanity's benefactor